2020
DOI: 10.1002/ccd.29439
|View full text |Cite
|
Sign up to set email alerts
|

Dedicated plug based closure for large bore access –The MARVEL prospective registry

Abstract: Objectives To study safety and performance of the MANTA Vascular closure device (VCD) under real world conditions in 10 centers. Background The MANTA is a novel plug‐based device for large bore arteriotomy closure. Methods We included all eligible patients who underwent transfemoral large bore percutaneous procedures. Exclusion criteria were per operator's discretion and included severe calcification or marked tortuosity of the access vessel, presence of marked obesity/cachexia or a systolic blood pressure abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 17 publications
6
29
1
Order By: Relevance
“…Indeed, logistic regression revealed that the chance of suffering a major complication is 3.6-fold higher among women than among men. This finding is consistent with previous studies, 4,10,12,26,27 and might be based on gender-specific differences in anatomy. Our analysis shows that female patients have a significantly shorter CFA, a smaller vessel angulation at the puncture site, a shorter minimal luminal diameter, and smaller vessel perimeter and area.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Indeed, logistic regression revealed that the chance of suffering a major complication is 3.6-fold higher among women than among men. This finding is consistent with previous studies, 4,10,12,26,27 and might be based on gender-specific differences in anatomy. Our analysis shows that female patients have a significantly shorter CFA, a smaller vessel angulation at the puncture site, a shorter minimal luminal diameter, and smaller vessel perimeter and area.…”
Section: Discussionsupporting
confidence: 93%
“…However, the major vascular complication rate of 4% in the recently published MARVEL prospective registry and in the retrospective study by van Wiechen et al is comparable to our results. 10,11 Similar findings were also observed in the SAFE MANTA trial and in the meta-analysis by Nuis et al 12,20 The comparison of the minor complication rates of the aforementioned studies is similar to the broad diversity of the major adverse events. [9][10][11][12][13][14][15][16][17][18][19][20][21][22] In the present study, we only observed 1% of minor complications, which strongly differs from most of the previous analyses.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations